2019
DOI: 10.1186/s12917-018-1751-2
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic glycoengineering of Apx toxin fragments in the development of Actinobacillus pleuropneumoniae glycoconjugate vaccines

Abstract: BackgroundActinobacillus pleuropneumoniae is the causative agent of porcine pleuropneumonia and represents a major burden to the livestock industry. Virulence can largely be attributed to the secretion of a series of haemolytic toxins, which are highly immunogenic. A. pleuropneumoniae also encodes a cytoplasmic N-glycosylation system, which involves the modification of high molecular weight adhesins with glucose residues. Central to this process is the soluble N-glycosyl transferase, ngt, which is encoded in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…2 and Supplementary Table 4). Previous works indicate that in A. pleuropnemoniae , the glucose installed by ApNGT is modified by the polymerizing Apα1-6 glucosyltransferase to form N -linked dextran 29 and that this structure could be a useful vaccine antigen 16,35 . Recent work also showed that the β1-4 galactosyltransferase LgtB from Neisseria meningitis (NmLgtB) can modify an ApNGT-installed glucose in E. coli , forming N -linked lactose (Galβ1-4Glc-Asn) 28 .…”
Section: Resultsmentioning
confidence: 99%
“…2 and Supplementary Table 4). Previous works indicate that in A. pleuropnemoniae , the glucose installed by ApNGT is modified by the polymerizing Apα1-6 glucosyltransferase to form N -linked dextran 29 and that this structure could be a useful vaccine antigen 16,35 . Recent work also showed that the β1-4 galactosyltransferase LgtB from Neisseria meningitis (NmLgtB) can modify an ApNGT-installed glucose in E. coli , forming N -linked lactose (Galβ1-4Glc-Asn) 28 .…”
Section: Resultsmentioning
confidence: 99%
“… 168 Other studies have developed short, optimized GlycTag sequences for NGT 80 and have shown that the modification of a target protein with these GlycTags (such as GGNWTT) can successfully direct efficient NGT glycosylation of diverse recombinant proteins in vivo and in vitro . 80 , 160 , 173 Later studies have found that the single glucose residue installed by NGT can be elaborated to a dextran polymer 160 (which could be useful for vaccines against pathogenic bacteria that use NGTs to adhere to human cells), polysialic acids 131 (which may prolong the serum-half-life of small therapeutic proteins), N -acetyllactosamine (LacNAc), 174 , 175 and other fucosylated and sialylated forms of lactose 174 , 175 by overexpression of elaborating GTs within the cell. 131 This sequential elaboration technique may also allow an NGT-based system to circumvent the limits on glycan structure found in OST systems.…”
Section: Synthetic Glycosylation Systemsmentioning
confidence: 99%
“…Recently, several N - and O -linked glycosylation systems that function in the bacterial cytoplasm have been discovered. These systems often glycosylate extracellular adhesion and autotransporter proteins that facilitate adherence of pathogenic bacteria to human cells. N -glycosyltransferases (NGTs) are one such class of enzymes that have been recently characterized ,, and have elicited great interest from the glycoengineering community for their ability to initiate N -linked glycosylation in the bacterial cytoplasm when heterologously expressed in E. coli . ,,,,,, NGTs bear structural homology to eukaryotic OGTs, but were first identified as part of an extracellular adhesion operon in Haemophilus influenzae , founding a new functional class of GTs that install monosaccharides onto asparagine residues in the cytoplasm using UDP-Glc or UDP-Gal as soluble sugar donors . In some species, the single glucose residues installed by NGTs are extended into a dextran polymer by a glucose polymerase (α 1,6 GlcT) .…”
Section: The “Parts” Of Synthetic Glycobiology: An Engineer’s Guide T...mentioning
confidence: 99%
See 1 more Smart Citation
“…5658 Much of the research with this enzyme has focused on biochemical characterisation and its potential for vaccine assembly is currently being explored. 59…”
Section: Extending the Capabilities Of Pgctmentioning
confidence: 99%